Global trends in interest rates - Marco Del Negro; Domenico Giannone; Marc Paolo Giannoni; Andrea Tambalotti (Federal Reserve Bank of New York, 2018)
The trend in the world real interest rate for safe and liquid assets fluctuated close to 2 percent for more than a century, but has dropped significantly over the past three decades. This decline has been common among advanced economies, as trends in real interest rates across countries have converged over this period. It was driven by an increase in the convenience yield for safety and liquidity and by lower global economic growth.
Keywords: E43; E44; F31; G12; 330; world interest rate; convenience yield; interest rate parity; VAR with common trends; Realzins; Wirtschaftliche Konvergenz; Liquidität; Wirtschaftliche Sicherheit; Schätzung; Industrieländer; USA